2015
DOI: 10.3390/md13085402
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effect of Algae-Derived Lipid Extracts on Lipopolysaccharide (LPS)-Stimulated Human THP-1 Macrophages

Abstract: Algae contain a number of anti-inflammatory bioactive compounds such as omega-3 polyunsaturated fatty acids (n-3 PUFA) and chlorophyll a, hence as dietary ingredients, their extracts may be effective in chronic inflammation-linked metabolic diseases such as cardiovascular disease. In this study, anti-inflammatory potential of lipid extracts from three red seaweeds (Porphyra dioica, Palmaria palmata and Chondrus crispus) and one microalga (Pavlova lutheri) were assessed in lipopolysaccharide (LPS)-stimulated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 71 publications
9
104
2
Order By: Relevance
“…Glycolipids have already been identified for members of the Rhodophyta (red seaweeds), namely in the genus Gracilaria [21,30,40,41,42]. However, the majority of published works only identified a few species of glycolipids, either by using offline TLC–MS [30,40,42,43] or selected solvent extraction and MS analysis [15,20,29]. More recently, a detailed profile of Chondrus crispus was reported using LC–MS and MS/MS [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycolipids have already been identified for members of the Rhodophyta (red seaweeds), namely in the genus Gracilaria [21,30,40,41,42]. However, the majority of published works only identified a few species of glycolipids, either by using offline TLC–MS [30,40,42,43] or selected solvent extraction and MS analysis [15,20,29]. More recently, a detailed profile of Chondrus crispus was reported using LC–MS and MS/MS [26].…”
Section: Resultsmentioning
confidence: 99%
“…Polar lipids are nowadays recognized as an important reservoir of fatty acids with nutritional value, e.g., n -3 FAs [5,6], and they are also considered high-value novel lipids with beneficial health effects such as antitumoral [7,8], antiviral [8,9], antifungal [10], antibacterial [11], and anti-inflammatory [11,12], with potential applications in the nutraceutical and pharmaceutical industries [7,8,11]. However, in spite of their recognized potential, they are still scarcely studied [12,13,14,15]. Some studies reported that polar lipids isolated from seaweeds can promote growth-inhibiting effects on human hepatocellular carcinoma cell lines (HepG2) [16] and thus can act as inhibitors of DNA polymerases with capability to inhibit tumor cell proliferation [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the arrays were previously described [22]. Gene expression profiling for human cytokines/chemokines was performed by using an in-house PCR array that consisted of 89 genes [23].…”
Section: Methodsmentioning
confidence: 99%
“…Natural products are alternatives to these drugs and offer hope for discovering bioactive lead compounds that may be developed into drugs for treatment of inflammatory disorders [12]. Plenty of unique marine natural products and their derivatives, such as sesquiterpenoid, polysaccharide, steroid/sterol and alkaloid, are found to manifest an anti-inflammatory action [13,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%